Probing the trapping and thermal activation dynamics of excitons at single twin defects in GaAs–AlGaAs core–shell nanowires - Daniel Rudolph; Lucas Schweickert; Stefanie Morkötter; Lukas Hanschke; Simon Hertenberger; Max Bichler; Gregor Koblmüller; Gerhard Abstreiter; Jonathan J Finley (New Journal of Physics, 2013)
Time resolved and time-integrated photoluminescence (PL) spectroscopy is used to investigate the trapping and thermal activation dynamics of excitons bound to single twin defects in individual GaAs–AlGaAs core–shell nanowires. The GaAs core exhibits two distinct spectral emission features that are attributed to free and bound excitons. Time resolved measurements reveal lifetimes of $τ _{{\rm{FE}}} \sim 1.4 \,{\rm{ns}}$ and $τ _{{\rm{BE}}} \sim 4.0 \,{\rm{ns}}$ for the free and bound excitons, respectively. For temperatures above 30 K, the global PL intensity is quenched due to non-radiative carrier recombination. In contrast, for temperatures below 20 K we observe clear evidence for thermal detrapping of bound excitons into the continuum. By comparing the time-resolved PL spectra with a two-level rate equation model, quantitative values are obtained for both the exciton trapping and detrapping rates. Our data is consistent with a temperature independent exciton trapping rate >20 GHz that dominates the population dynamics of bound excitons at T = 6 K. At elevated temperature, the detrapping rate is found to adhere to a thermally activated behavior characterized by a thermal activation energy of $E_{\rm{A}} = 5.8 ± 1.0 \,{\rm{meV}}$ , very close to the energy spacing of bound and free exciton emission features. This observation implies that bound excitons are thermally activated into the excitonic continuum without the need to overcome additional energetic barriers.